Shakespeare and the Poet's Life. - Schmidgall, Gary (The University Press of Kentucky, 2015)
Shakespeare and the Poet's Life explores a central biographical question: why did Shakespeare choose to cease writing sonnets and court-focused long poems like The Rape of Lucrece and Venus and Adonis and continue writing plays? Author Gary Schmidgall persuasively demonstrates the value of contemplating the professional reasons Shakespeare -- or any poet of the time -- ceased being an Elizabethan court poet and focused his efforts on drama and the Globe. Students of Shakespeare and of Renaissance poetry will find Schmidgall's approach and conclusions both challenging and illuminating.